Development of a Cloud Computing-Based Collaboration Information System - Anwar, Anwar; Zulman, Muhammad Reza; Arhami, Muhammad; Nahar, Nahar; Safriadi, Safriadi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The rapid advancement of information and communication technology has created a demand for efficient and effective information systems to facilitate collaboration among institutions. This study develops a cloud computing-based collaboration information system designed to enhance real-time communication, data management, and collaboration among users. The system comprises key modules, including collaboration management, document management, and integrated collaboration features. Testing involved various scenarios with 10 to 100 active users simultaneously, revealing that the system maintained stable performance with response times under 3 seconds for each user request. Furthermore, security assessments utilizing encryption protocols and two-factor authentication confirmed that the managed data is protected from external threats. The findings underscore the system's potential to improve collaborative efficiency while ensuring data security, making it a valuable solution for future collaborative initiatives.